Controlled Synthesis of Multifunctional Coatings by Micro-Arc Oxidation Method - Pecherskaya, Ekaterina Anatol'evna; Golubkov, Pavel Evgen'evich; Karpanin, Oleg Valentinovich; Safronov, Maxim Igorevich; Zinchenko, Timur Olegovich; Artamonov, Dmitriy Vladimirovich (International journal of embedded and real-time communication systems, 2022)
The article is devoted to the development of the methodology for the controlled synthesis of protective coatings by the micro-arc oxidation method in order to improve the efficiency of this technology and the quality of the obtained oxide layers. Methodology includes a mathematical model of a galvanic cell based on an equivalent electrical circuit, as well as a model of the interconnections between the technological parameters of the micro-arc oxidation (MAO) process and the properties of the obtained oxide layers based on graph theory. The indicated dependences are formalized using methods of regression and correlation analysis of experimental data. A technique for the controlled synthesis of MAO coatings using the obtained regression equations is proposed. The structure and functioning algorithm of an intelligent automated system for the controlled synthesis of MAO coatings are developed. A prototype of this system was used to obtain experimental dependences of reaction parameters on the influence parameters of the micro-arc oxidation process.